Persistent Pain after Dental Surgery - Renton, Tara (Rev Pain, 2011)
This article aims to cover post surgical trigeminal neuropathy and other conditions related to chronic trigeminal pain not specifically covered elsewhere in this series. Is estimated to occur in 4–5% of patients overall, considerably less compared with other site surgeries. Due to the high volume surgery undertaken in this region chronic post surgical pain remains common. Relatively few clinicians are aware of this condition and as a result it is frequently poorly managed.